2020
DOI: 10.3390/ma13092055
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Mortars Based on Different Binders and Containing a Novel Sustainable Phase Change Material (PCM)

Abstract: Increasing concerns about climate change and global warming bring about technical steps for the development of several energy-efficient technologies. Since the building sector is one of the largest energy users for cooling and heating necessities, the incorporation of a proper energy-efficient material into the building envelopes could be an interesting solution for saving energy. Phase change material (PCM)-based thermal energy storage (TES) seems suitable to provide efficient energy redistribution. This is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In previous research [ 31 , 50 , 51 , 52 ], a novel, sustainable, form-stable PCM was produced starting from a low-toxicity/low-flammability PEG polymer of medium molecular weight (PEG 1000) [ 50 ]. This polymer was easily included in waste natural material: flakes of porous stone derived from extraction and processing of the stone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research [ 31 , 50 , 51 , 52 ], a novel, sustainable, form-stable PCM was produced starting from a low-toxicity/low-flammability PEG polymer of medium molecular weight (PEG 1000) [ 50 ]. This polymer was easily included in waste natural material: flakes of porous stone derived from extraction and processing of the stone.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainable and low-cost product was added to mortars based on different binders (aerial lime, hydraulic lime, gypsum, or concrete) [ 31 , 51 ], which were demonstrated to be efficient in reducing indoor temperature fluctuations, especially in warm seasons and in buildings located in Mediterranean regions. It was, in fact, found that PEG 1000 does not undergo its phase change at “low” temperatures, which means during the winter season [ 52 ]. In order to extend the temperature range and make the PCM effective even at low temperatures, a new form-stable PCM was produced.…”
Section: Introductionmentioning
confidence: 99%
“…With the rising demand for building thermal comfort and high-quality indoor thermal environment, building energy consumption has been growing continuously in recent years [ 1 , 2 , 3 , 4 ]. Thus, various environment-friendly technologies have been proposed to enhance building energy efficiency and reduce carbon dioxide emissions [ 5 , 6 ]. Among various technologies, the use of phase change materials (PCMs) has gained more and more attention, as they have high energy storage density and can be operated within a small temperature range during the phase change conversion process [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of thermal performance, many studies have confirmed that in addition to the energy-savings of buildings, thermal performance and comfort are improved when PCMs are used in cement mortars as addition to or replacement of the aggregates content. PCMs are also considered a good and economical solution to the thermal-energy efficiency problem of buildings [2,5,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%